LA METODOLOGÍA ACTIVA Y PARTICIPATIVA DE ENSEÑANZA Y SU INCIDENCIA EN EL DESARROLLO DEL APRENDIZAJE AUTÓNOMO EN LOS ESTUDIANTES DE OCTAVO, NOVENO Y DÉCIMO AÑO DE EDUCACIÓN BÁSICA DE LA UNIDAD EDUCATIVA A DISTANCIA DE LOS RÍOS, EXTENSIÓN SAN CAMILO DEL CANTÓN QUEVEDO, PROVINCIA DE LOS RÍOS. - Gaibor González, Silvia Berónica (2014)
This study brought it out on the premises of the educational unit to distance the Ríos, extension San Camilo Quevedo Canton, Los Ríos province, in order to determine the incidence of the methodology active and participative teaching in the development of autonomous learning in students of basic education, for which it was considered a sample of 193 studentsin the same way we used a population of 2 directors and 12 teachers, with the purpose of achieving the object of study and discussion of results, design a guide of autonomous learning, based on the use of active and participatory strategies in accordance with the requirements of the basic distance education. To reach attainment of the overall objective of the present study, the level of domain of active and participatory methodologies of teachers in the educational unit of basic education was determined to distance of the Ríos San Extension Camilo, in the same way, were identified as students of basic education are autonomous learning. With the results obtained through the field survey and analysis of the cited theories according to the variables of the object of study, it was concluded that there is a need to implement strategic participatory and active to improve the development of autonomous learning in the educational unit to distance learners.